Trust and Television in Globalizing India - McMillin, Divya (Television Histories in Asia: Issues and Contexts, 2015)
Writing a history of Indian television immediately begs the question, how do we want it read? Exhaustive chronological treatments anchor the field (Kumar 2000 ), ideological examinations reveal a Hindu-centric nation with serious consequences for religious and gender minorities (Rajagopal 1996 ; Mitra 1993 ; Van der Veer 1997 ), development analyses demonstrate the failures of a socialist state (F ü risch and Shrikhande 2007 ), and audience studies reveal complex negotiations among multiple identity positions (Mankekar 1999 ). These critical approaches to the study of television in India rightly expose power differentials that facilitate, through the centuries, the inequities of interwoven structures of imperialism, colonialism, casteism, and capitalist patriarchy. Most importantly, they highlight the chronic condition of distrust in postcolonial societies, making it highly challenging to legitimize profi table connections to global circuits as they modernize under the very conditions that once constrained them.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Working Women and Romance on Japanese Television Dramas: Changes since Tokyo Love Story - Freedman, Alisa (Television Histories in Asia: Issues and Contexts, 2015)
Since their development in their current format in the early 1990s as a means to attract female viewers in their twenties, Japanese prime-time television dramas-known commonly as ‘ dorama ’ 1 —have featured working women. Even police procedurals, medical dramas, and serials based on ‘ shojo manga ’ (graphic novels for girls) depict women working outside the home. The dorama most watched by Japanese audiences older than age 25, and those that continue to attract global fans, present the daily lives of independent women working in Tokyo. The protagonists enact fantasies about female professionals while depicting real issues facing the larger generations they represent. Viewers may not want to be these characters, but they can see aspects of themselves in them.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; Japon (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

The Television of Intervention: Mediating Patron–Client Ties in the Philippines - Corpus Ong, Jonathan (Television Histories in Asia: Issues and Contexts, 2015)
Similar to the other countries discussed in this volume, elite dominance over mass media has been a main characteristic of Filipino history. Foreign-educated Filipino intellectuals from wealthy families founded the early periodicals that demanded reform and/or independence from Spanish colonization in the late nineteenth century (Anderson 1983 ). Today, ‘old rich’ landowning families own and operate television networks, radio stations, and newspapers not only as part of prestigious and profi table media conglomerates, but also in connection with their interests in industries as varied as oil and agriculture to insurance, shipping, and mining.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude de la réception; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; Philippines (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)